APPLICATION AND COUNTRY CASE STUDY - Valmonte-Santos, Rowena; Meinzen-Dick, Ruth S. (2023)
Valmonte-Santos, Rowena A. and Meinzen-Dick, Ruth. 2023. Application and Country Case Study. PowerPoint presentation given to students of AG 4390/AG 5371: Global Agriculture Leadership Academy. Department of Agriculture, Texas State University, San Marcos, Texas, March 24, 2023.